Mycological Culture Profile and Clinical Predictors of Culture Positivity in Dermatophytosis: A Four-Year Retrospective Study at a Tertiary Referral Hospital in Bali, Indonesia - Ni Luh Putu Ratih Vibriyanti Karna; Antonio Orson Ongkowidjojo; Ida Ayu Ketut Ariningsih (HM Publisher, 2026)
Background: Dermatophytosis is the commonest superficial mycosis, yet the aetiological spectrum in eastern Indonesia and the determinants of a positive fungal culture remain poorly characterised. We aimed to describe the mycological culture profile and identify predictors of culture positivity at a tertiary referral centre in Bali. Methods: This STROBE-compliant retrospective cross-sectional study analysed 214 consecutively sampled patients with dermatophytosis at the Dermatology and Venereology clinic of Ngoerah Hospital, Denpasar, between January 2020 and December 2023. Potassium-hydroxide (KOH) microscopy and Sabouraud culture data were extracted from records. Proportions carried 95% Wilson confidence intervals (CI); associations were assessed by chi-square/Fisher tests with odds ratios and Cramér's V, followed by multivariable logistic regression (adjusted odds ratio [aOR], Nagelkerke R²) and receiver-operating-characteristic analysis. Results: Mean age was 42.7 years and the male-to-female ratio 1.68:1; Fitzpatrick phototype IV predominated (51.9%). Culture was positive in 138 patients (64.5%; 95% CI 57.9–70.6). Trichophyton rubrum was the leading isolate (50.0%; 95% CI 41.8–58.2), followed by the T. mentagrophytes complex (15.9%) and Microsporum canis (10.1%); anthropophilic species comprised 81.2%. KOH positivity (aOR 5.20; 95% CI 2.27–11.87; p<0.001) independently predicted culture positivity, whereas prior antifungal use was protective (aOR 0.30; 95% CI 0.13–0.65; p=0.002); the model discriminated well (AUC 0.785; 95% CI 0.715–0.855). Conclusion: Dermatophytosis in Bali is dominated by anthropophilic T. rubrum, and culture yield is governed chiefly by prior antifungal exposure and KOH status, supporting a stewardship-oriented diagnostic pathway in which culture is prioritised for KOH-positive, treatment-naive and recalcitrant presentations.